Formulation Development of Nimesulide Tablets by Wet Granulation and Direct Compression Methods Employing Starch Citrate - Chowdary, K.P.R.; Enturi, Veeraiah; Aluru, Ajay (Asian Journal of Chemistry, 2012)
Nimesulide, a widely prescribed antiinflammatory analgesic drug belongs to BCS class II and exhibit low and variable oral bioavailability due to its poor solubility and dissolution rate. The objective of the present study is to develop nimesulide rapidly dissolving tablet formulations by wet granulation and direct compression methods employing starch citrate, a new modified starch. As per FDA guidelines on biowaivers, drug products containing weakly acidic BCS class II drugs with a dissolution of > 85 % in 0.5 h are eligible for biowaiver. Hence a dissolution of > 85 % in 0.5 h is taken as target dissolution to achieve in the formulation development of nimesulide tablets. Starch citrate prepared by reacting potato starch with citric acid at elevated temperatures was insoluble in water and has good swelling (1500 %) property without pasting or gelling when heated in water. In the micromeritic evaluation, the angle of repose and compressibility index values revealed the excellent flow characteristic of starch citrate prepared. All the physical properties studied indicated that starch citrate is a promising pharmaceutical excipient in tablets. Nimesulide rapidly dissolving tablets with >85 % dissolution in 0.5 h could be formulated employing starch citrate as directly compressible vehicle by direct compression method (BF3) and also employing nimesulide-starch citrate (1:2) solid dispersion by wet granulation method (BF4). Formulations BF3 and BF4 respectively gave 90.25 % and 99.73 % dissolution in 0.5 h fulfilling the target dissolution requirement for biowaiver.